AN ANALYSIS OF TEACHERS’ TALK IN AN EFL CLASSROOM - Nurul Aisyah (Journal of English and Education, 2016)
This research was aimed at discovering teachers’ talk category occurred the most in an EFL classroom and reasons for teacher in choosing categories that occurred. The data were obtained through observation conducted in the 10th grade of an EFL classroom at BPI 1 Senior High School as well as teacher interview. The observation was conducted in five meetings along with video recording. The data were then analyzed by using framework of teachers’ talk proposed by Flanders (1970) namely Flanders Interaction Analysis Categories (FIAC). The findings showed that all categories of teachers’ talk occurred in the classroom with varied percentage of occurrence. From those various categories, asking questions was the category occurred the most in the classroom. Nevertheless, the occurred categories happened naturally with the consideration of learning situation that takes place. In addition the analysis of teachers’ talk in the classroom would be beneficial for teachers to plan and conduct enhanced learning situation.